Giant Goos–Hänchen shift in scattering : the role of interfering localized plasmon modes - Ghosh, N. (2014)
The longitudinal and transverse beam shifts, namely, the Goos–Hänchen (GH) and the Spin-Hall (SH) shifts are usually observed at planar interfaces. It has recently been shown that the transverse SH shift may also arise due to scattering of plane waves. Here, we show that analogous in-plane (longitudinal) shifts also exist in the scattering of plane waves from micro/nano systems. We study both the GH and the SH shifts in plasmonic metal nanoparticles/nanostructures and dielectric micro-particles employing a unified framework that utilizes the transverse components of the Poynting vector of the scattered wave. The results demonstrate that the interference of neighboring resonance modes in plasmonic nanostructures (e.g., electric dipolar and quadrupolar modes in metal spheres) leads to great enhancement of the GH shift in scattering from such systems. We also unravel interesting correlations between these shifts with the polarimetry parameters, diattenuation and retardance.